The non-interrogative sentence-final particle ne 呢 in Mandarin (Linguistics in Amsterdam, 2021)
The meanings and functions of sentence-final particles in Mandarin are constantly under debate. The sentence-final particle ne 呢 (henceforth: SF ne) is one of these particles. This paper is devoted to arguing that the non-interrogative SF ne is a contradiction marker, signaling that the currently stated message is in contradiction with a previously existing assumption. In sentences that SF ne combines with, there is always, implicitly or explicitly, a contradicting negative or positive assumption. This paper also discusses how contradiction should be treated in Functional Discourse Grammar (FDG). It is argued that SF ne is an operator of contradiction under the category of polarity, operating at the layer of the Communicated Content at the Interpersonal Level. It is also suggested that a sub-category of contradiction should be added to the category of polarity in the framework of FDG.